2020
DOI: 10.3390/ijerph17030703
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Preventive Measures for Oral Health Care among Male Intermediate Schoolchildren in Abha, Saudi Arabia

Abstract: The aims of this study were to evaluate oral health knowledge and assess the practice of preventive measures for oral health care among intermediate schoolchildren in Abha, Saudi Arabia. Information about oral health was collected through a questionnaire containing closed-ended questions, which was distributed to children of six randomly selected intermediate schools. Most (82.3%) of the schoolchildren were aware that good oral health is important for general health. The priority for oral health information wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 25 publications
2
47
2
4
Order By: Relevance
“…Periodic dental checkups are important in preventing oral disease, educating patients, and encouraging them to maintain good oral hygiene habits. 6,[29][30][31][32] For example, in 2020, Covello et al found that periodic followups can even prevent oral piercing complications. 33 Only a minority of our participants used electric toothbrushes, which is consistent with the results of previous studies that showed a low frequency of electric toothbrush users among students and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Periodic dental checkups are important in preventing oral disease, educating patients, and encouraging them to maintain good oral hygiene habits. 6,[29][30][31][32] For example, in 2020, Covello et al found that periodic followups can even prevent oral piercing complications. 33 Only a minority of our participants used electric toothbrushes, which is consistent with the results of previous studies that showed a low frequency of electric toothbrush users among students and adults.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, health teachers were asked to teach students . The ndings indicated the signi cance of training teachers to teach self-regulation skills in class (12). According to the National Oral Health Care Program, students follow the suit when teachers brush their teeth, which becomes a daily exercise routine.…”
Section: Discussionmentioning
confidence: 98%
“…(9). In general, health education programs are used for creating new behaviors, as well as maintaining healthy behaviors which can promote individual and community health (12). In this regard, education and entertainment should be integrated to create a happy context for learning among children (9).…”
mentioning
confidence: 99%
“…[ 4 5 ] Oral hygiene is poor and introduced late in the life of Saudis. [ 6 7 ] Parents’ oral health status can affect their children's’ risk of caries. [ 8 ] Dental caries are common among Saudi children.…”
Section: Introductionmentioning
confidence: 99%